A review of drug delivery systems based on nanotechnology and green chemistry: green nanomedicine - Jahangirian H (Dove Medical Press, 2017)
Hossein Jahangirian,1 Ensieh Ghasemian Lemraski,2 Thomas J Webster,1 Roshanak Rafiee-Moghaddam,3 Yadollah Abdollahi4 1Department of Chemical Engineering, Northeastern University, Boston, MA, USA; 2Department of Chemistry, Faculty of Science, Ilam University, Ilam, Iran; 3School of Chemical Sciences and Food Technology, Faculty of Science and Technology, Universiti Kebangsaan Malaysia, Selangor, 4Department of Electrical Engineering, Faculty of Engineering, University of Malaysia, Kuala Lumpur, Malaysia Abstract: This review discusses the impact of green and environmentally safe chemistry on the field of nanotechnology-driven drug delivery in a new field termed “green nanomedicine”. Studies have shown that among many examples of green nanotechnology-driven drug delivery systems, those receiving the greatest amount of attention include nanometal particles, polymers, and biological materials. Furthermore, green nanodrug delivery systems based on environmentally safe chemical reactions or using natural biomaterials (such as plant extracts and microorganisms) are now producing innovative materials revolutionizing the field. In this review, the use of green chemistry design, synthesis, and application principles and eco-friendly synthesis techniques with low side effects are discussed. The review ends with a description of key future efforts that must ensue for this field to continue to grow. Keywords: green chemistry, cancer, drug delivery, nanoparticle